Interface reaction between electroless Ni–Sn–P metallization and lead-free Sn–3.5Ag solder with suppressed Ni3P formation - Yang, Ying (2014)
The voids formed in the Ni3P layer during reaction between Sn-based solders and electroless Ni–P metallization is an important cause of rapid degradation of solder joint reliability. In this study, to suppress formation of the Ni3P phase, an electrolessly plated Ni–Sn–P alloy (6–7 wt.% P and 19–21 wt.% Sn) was developed to replace Ni–P. The interfacial microstructure of electroless Ni–Sn–P/Sn–3.5Ag solder joints was investigated after reflow and solid-state aging. For comparison, the interfacial reaction in electroless Ni–P/Sn–3.5Ag solder joints under the same reflow and aging conditions was studied. It was found that the Ni–Sn–P metallization is consumed much more slowly than the Ni–P metallization during soldering. After prolonged reaction, no Ni3P or voids are observed under SEM at the Ni–Sn–P/Sn–3.5Ag interface. Two main intermetallic compounds, Ni3Sn4 and Ni13Sn8P3, are formed during the soldering reaction. The reason for Ni3P phase suppression and the overall mechanisms of reaction at the Ni–Sn–P/Sn–3.5Ag interface are discussed.